Type of Taboo Words Used by The Characters in Me Time Movie - Lily Antari; Santika, I Dewa Ayu Devi Maharani (Institut Pariwisata dan Bisnis Internasional, 2025)
The use of taboo words is prohibited in some places or situations. But even the use of taboo words are prohibited, a lot of people still use them, especially for teenagers. They use taboo words to express their emotion. Taboo words are commonly used in movies or films with comedy genres. The aim of this research is focused on analyzing the type of taboo word that is used by the character in the Me Time movie. The researcher used this film as the data source because it consists of a lot of taboo words used by the characters because this film has a comedy genre. The researcher used an observation method in collecting the data by watching and observing the movie then taking note of the important word. This research used the theory proposed by Batistella (2005) to analyze the data. According to Batistella (2005), there are 4 types of taboo words: Profanity, Epithet, Vulgarity, and Obscenity. The result of this research is that the highest frequency type of taboo word found is Vulgarity with 7 words, and the second is Profanity with 5 words and the third is Obscenity with 2 data and the lowest frequency is Epithet with only one data.